A 50-year-old man with low back pain, type 2 diabetes mellitus, grade I hypertension, and dyslipidemia with occupational risk factors (private sector worker), unhealthy lifestyle, and genetics - Izzatil Muslimah, Tsania; Setijowati, Nanik (Jurnal Ilmu Kedokteran Keluarga, 2026)
Background: Multiple chronic diseases such as diabetes, hypertension, dyslipidemia, and low backpain significantly affect quality of life. Family medicine provides a holistic management approach.Objective: To evaluate the implementation of a Family Health Care Project in a patient with multiplechronic conditions.Method: A case study was conducted on a 50-year-old male with low back pain, type 2 diabetesmellitus, grade I hypertension, and dyslipidemia. Data were collected through anamnesis, physicalexamination, laboratory tests, family assessment, and home visits. Interventions included education,pharmacological therapy, lifestyle modification, and a family conference.Results: The patient presented risk factors such as heavy physical work, unhealthy lifestyle, andfamily history. Findings included fasting blood glucose 192 mg/dL, random blood glucose 275mg/dL, total cholesterol 249 mg/dL, triglycerides 185 mg/dL, and blood pressure 149/95 mmHg. AFamily APGAR score of 8 indicated good family functioning. Interventions improved patient'sunderstanding but medication adherence remained low.Conclusion: The Family Health Care Project improved family support and patient understanding,although treatment adherence requires further strengthening.